1995
DOI: 10.1017/s0007485300032946
|View full text |Cite
|
Sign up to set email alerts
|

Orientation by gravid Australian sheep blowflies, Lucilia cuprina (Diptera: Calliphoridae), to fleece and synthetic chemical attractants in laboratory bioassays

Abstract: Gravid females of Lucilia cuprina (Wiedeman) in a laboratory cage orientated positively to samples of fleece. Newly-wetted fleece was significantly more attractive than dry fleece, an effect resulting from the action of water on the fleece and not just addition of water vapour to the volatile fleece kairomones. Fleece contaminated with serous exudate, resulting from myiasis by L. cuprina, was much more attractive than wet, uncontaminated fleece from the same sheep. Kairomones from wetted fleece consistently au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…(1994a). Eisemann (1995) showed that the activity of gravid female L. cuprina was three times greater in the presence of wet sheep than dry sheep. No equivalent data are available for L. sericata , but it is assumed that the affects of sheep wetness on the behaviour of this fly species is equivalent to that of L. cuprina .…”
Section: Methodsmentioning
confidence: 99%
“…(1994a). Eisemann (1995) showed that the activity of gravid female L. cuprina was three times greater in the presence of wet sheep than dry sheep. No equivalent data are available for L. sericata , but it is assumed that the affects of sheep wetness on the behaviour of this fly species is equivalent to that of L. cuprina .…”
Section: Methodsmentioning
confidence: 99%
“…In recent work, gravid L. cuprina were found to be more attracted to decaying liver than to fresh liver, although the strongest oviposition behaviour was observed on fresh liver (G. Yan, unpublished data). Similarly, gravid flies do not show a preference in attraction between wet and dry wool, although there is a correlation between egg laying and moisture content (Eisemann, ; A. C. Schlink, G. Yan & J. C. Greeff, unpublished data). It is therefore clear that a greater attractiveness for a resource does not guarantee oviposition, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…First, only fleece odour was considered as a factor in the present study and so fleece were samples in the season of least flystrike to exclude the effect of other important factors (e.g. dags, urine, faeces and moisture) that are very likely to attract L. cuprina (Eisemann, ; Greeff et al ., ). Previous studies have shown that the attractiveness of wool samples from fly‐struck sheep declines rapidly over time after removal from the sheep (Mackerras & Mackerras, ), ostensibly as a result of the loss of critical attractive volatile compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The bioassay described here can be contrasted with the olfactometer of Urech et al (1994) and laboratory trapping as described by Eisemann (1985Eisemann ( , 1995, both of which have been used to demonstrate responses to odours in L.cuprina. These two methods tested whether L.cuprinu would congregate towards a concentration of odour, but the mechanism, whether by anemotaxis, chemotaxis, kineses or a combination of all three was not differentiated.…”
Section: Discussionmentioning
confidence: 99%